Targeting CD16A on NK cells and GPC3 in hepatocellular carcinoma: development and functional validation of a therapeutic bispecific antibody - Chen, Liu; Zhu, Yuankui; Feng, Mingqian; Zuo, Dianbao; Chen, Guoping; Ji, Kangkang (Frontiers in Immunology, 2025)
IntroductionAdvanced hepatocellular carcinoma (HCC) poses significant therapeutic challenges due to chemotherapy resistance and limited efficacy of current targeted therapies. To address this unmet need, we developed a bispecific antibody (BsAb) platform targeting CD16A on natural killer (NK) cells and glypican-3 (GPC3), a tumor-specific antigen overexpressed in 70% of HCC cases.MethodsHigh-affinity anti-CD16A single-chain variable fragments (scFvs) were selected via phage display, followed by engineering of Fc-stabilized BsAbs (MA4-hFc(N297A)-CD16A series) to minimize FcγR-mediated toxicity. Functional validation included binding kinetics (ELISA, flow cytometry, and fluorescence co-localization analysis), in vitro cytotoxicity assays (luciferase-based killing), and in vivo efficacy studies in Huh7 xenograft models. Synergy with sorafenib was assessed using CompuSyn analysis.ResultsThe lead candidate, MA4-hFc-CD16AM19, exhibited nanomolar affinity (EC50 < 10 nM for human CD16A) with no murine cross-reactivity. It demonstrated potent, dose-dependent cytotoxicity against GPC3+ HCC lines (HepG2/Huh7/Hep3B, IC50 = 15–35 ng/mL) via NK cell activation, surpassing conventional antibody-dependent cellular cytotoxicity (ADCC). Combined with sorafenib, MA4-hFc-CD16AM19 achieved synergistic tumor suppression (CI=0.41). In vivo, BsAb treatment (5 mg/kg) significantly inhibited tumor growth in xenograft models, correlating with enhanced intratumoral NK cell infiltration without toxicity.ConclusionThis study introduces three innovations: (1) a species-specific CD16A binder overcoming polymorphism limitations, (2) Fc domain engineering (N297A) to optimize stability and safety, and (3) a synergistic combination strategy with sorafenib. The results provide a translatable framework for GPC3+ solid tumor immunotherapy.